Impaired P2X1 receptor-mediated adhesion in eosinophils from asthmatic patients - Wright, A; Mahaut-Smith, M; Symon, F; Sylvius, N; Ran, S; Bafadhel, M; Muessel, M; Bradding, P; Wardlaw, A; Vial, C (American Association of Immunologists, 2016)
Eosinophils play an important role in the pathogenesis of asthma and can be activated by extracellular nucleotides released following cell damage or inflammation. For example, increased ATP concentrations were reported in bronchoalveolar lavage fluids of asthmatic patients. Although eosinophils are known to express several subtypes of P2 receptors for extracellular nucleotides, their function and contribution to asthma remain unclear. In this article, we show that transcripts for P2X1, P2X4, and P2X5 receptors were expressed in healthy and asthmatic eosinophils. The P2X receptor agonist α,β-methylene ATP (α,β-meATP; 10 μM) evoked rapidly activating and desensitizing inward currents (peak 18 ± 3 pA/pF at -60 mV) in healthy eosinophils, typical of P2X1 homomeric receptors, which were abolished by the selective P2X1 antagonist NF449 (1 μM) (3 ± 2 pA/pF). α,β-meATP-evoked currents were smaller in eosinophils from asthmatic patients (8 ± 2 versus 27 ± 5 pA/pF for healthy) but were enhanced following treatment with a high concentration of the nucleotidase apyrase (17 ± 5 pA/pF for 10 IU/ml and 11 ± 3 pA/pF for 0.32 IU/ml), indicating that the channels are partially desensitized by extracellular nucleotides. α,β-meATP (10 μM) increased the expression of CD11b activated form in eosinophils from healthy, but not asthmatic, donors (143 ± 21% and 108 ± 11% of control response, respectively). Furthermore, α,β-meATP increased healthy (18 ± 2% compared with control 10 ± 1%) but not asthmatic (13 ± 1% versus 10 ± 0% for control) eosinophil adhesion. Healthy human eosinophils express functional P2X1 receptors whose activation leads to eosinophil αMβ2 integrin-dependent adhesion. P2X1 responses are constitutively reduced in asthmatic compared with healthy eosinophils, probably as the result of an increase in extracellular nucleotide concentration.